Genome-Wide Analysis Reveals Genetic Potential for Aromatic Compounds Biodegradation of Sphingopyxis. (27th May 2020) - Yang, Fei; Feng, Hai; Massey, Isaac Yaw; Huang, Feiyu; Guo, Jian; Zhang, Xian
Abstract : Members of genus Sphingopyxis are frequently found in diverse eco-environments worldwide and have been traditionally considered to play vital roles in the degradation of aromatic compounds. Over recent decades, many aromatic-degrading Sphingopyxis strains have been isolated and recorded, but little is known about their genetic nature related to aromatic compounds biodegradation. In this study, bacterial genomes of 19 Sphingopyxis strains were used for comparative analyses. Phylogeny showed an ambiguous relatedness between bacterial strains and their habitat specificity, while clustering based on Cluster of Orthologous Groups suggested the potential link of functional profile with substrate-specific traits. Pan-genome analysis revealed that 19 individuals were predicted to share 1, 066 orthologous genes, indicating a high genetic homogeneity among Sphingopyxis strains. Notably, KEGG Automatic Annotation Server results suggested that most genes pertaining aromatic compounds biodegradation were predicted to be involved in benzoate, phenylalanine, and aminobenzoate metabolism. Among them, β -ketoadipate biodegradation might be the main pathway in Sphingopyxis strains. Further inspection showed that a number of mobile genetic elements varied in Sphingopyxis genomes, and plasmid-mediated gene transfer coupled with prophage- and transposon-mediated rearrangements might play prominent roles in the evolution of bacterial genomes. Collectively, our findings presented that Sphingopyxis isolates might be the promising candidates for biodegradation of aromatic compounds in pollution sites.